Variations in Trichoderma from Oil Palm Rhizosphere and its Biological Activities Against Ganoderma Boninense - Joseph, Hendry (2000)
A study on the distribution of Basal Stem Rot (BSR), frequency of isolation of Trichoderma spp. from oil palm rhizosphere, its biological activities and variations was attempted The incidence of BSR was found to be correlated to age of palm. The percentage of disease incidence (PDI) in mature palm (OP74) was comparatively higher than the middle age palm (OP89) or young palm (OP94). Frequency of isolation of Trichoderma spp. in the oil palm rhizosphere was found to be correlated to age of palm and disease incidence. Frequency of isolation (cfu/g soil) of Trichoderma spp. was higher in OP74 than OP89 or OP94. Four main species aggregates identified from oil palm rhizosphere were Trichoderma harzianum, Trichoderma virens, Trichoderma koningii and Trichoderma longibrachiatum. T. harzianum was the highest in distribution in all the areas sampled with T. longibrachiatum being the lowest in its population dynamic. In-vitro studies showed there were no variations in antagonistic activities between Trichoderma species aggregates. Meanwhile, a significant difference was observed within species aggregate as tested by dual culture and colony degradation tests, and production of volatile and non-volatile substances. Isolates TH1 of T. harzianum and TV1 of T. virens were observed to be consistent in their antagonistic and parasitic activities. Variations between and within species aggregate were studied usmg intracellular isozyme and RAPD-PCR. Peroxidase activity was able to identify variations between species aggregates, however less sensitive to detect variations within intraspecific groups. RAPD was useful and able to detect variations within intraspecific groups, however was not able to identify variations between species aggregates T. virens could hold the possibility to be develop as a potential biopesticide based on its diverse genetic nature and biological activities.